Análise Temporal da Incidência de Hanseníase e suas Reações em uma Região Hiperendêmica (Research, Society and Development, 2020)
Leprosy is a highly prevalent infectious disease in tropical regions and in low to medium income countries, with social inequality and poverty being important risk factors. As it is an infectious disease, transmitted through prolonged contact, the analysis of the spatial and spatial distribution of the disease and its determining factors in the populations are fundamental aspects for the establishment of public policies to combat the disease. The objective of this work was to carry out an epidemiological analysis of leprosy and its reactions, its temporal and spatial distribution, using geoprocessing techniques, in a hyper-endemic region of this disease. This is a retrospective observational cross-sectional study. The data were obtained from the Health Surveillance Database, of the National Medical Service System, in the municipality of Cáceres. The period from 2008 to 2018 was considered, evaluating sex, age, type of leprosy (Paucibacillary or Multibacillary), type of leprosy reaction and location of the notified patient, to perform geoprocessing. In all, 398 cases were reported in the period, with a mean age of 44.7 ± 16.9 years. Of the total, 59.11% of the reported cases were male. The most common clinical form was Multibacillary (53.3%), with the majority of these cases also being male (58.80%). Of the total cases, 12.56% of the patients had leprosy reactions, 46% of which were type 1, 36% of type 2 and 18% had both type 1 and type 2 reactions. From the use of geoprocessing, it was possible identify regions with a higher density of cases, which helps to guide future public policies for the treatment and prevention of the disease in the region.